2017
DOI: 10.1007/s00737-017-0786-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal flood-related stress and social support on offspring weight in early childhood

Abstract: The current study examined the moderating role of social support in the association between prenatal maternal stress (PNMS) and childhood body mass index (BMI) in the context of the Iowa floods of 2008. In addition, the mediating role of offspring birthweight was examined in the association between PNMS and childhood BMI. We recruited women from eastern Iowa who were pregnant in 2008 when disastrous floods occurred. Self-report measures of PNMS and cognitive appraisal of the flood's consequences were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…All studies were conducted in high‐income countries. Seven studies were conducted in Europe of which five of these were conducted in Denmark, four in Canada, three in the United States, and one in Australia. Except one study, which was a retrospective cohort study, all other studies were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies were conducted in high‐income countries. Seven studies were conducted in Europe of which five of these were conducted in Denmark, four in Canada, three in the United States, and one in Australia. Except one study, which was a retrospective cohort study, all other studies were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the cohort studies based on Project Ice Storm, pregnant women were exposed to the Quebec ice storm of January 1998. In the three Project Ice Storm studies and Iowa Flood study, the exposures were recorded mainly as subjective and objective prenatal maternal stress (PNMS) while one had cognitive appraisal of the natural disaster as exposure. Objective PNMS referred to the experience of threat, loss, scope, and changes due to the exposure to a particular event and subjective PNMS were experience of intrusive thoughts, hyperarousal, and avoidance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these effects were decreased if the pregnant woman had higher social support during the flood (Kroska et al. ). Therefore, providing increased social support to pregnant women during and after natural disasters may have positive consequences for generations after the specific traumatic event.…”
Section: Intergenerational Stress Resilience and Recovery: The Bodymentioning
confidence: 99%
“…Studies of the children born to mothers that experienced the stressful conditions of the floods in Iowa in 2008 have shown that these children had higher birth weights, increased body mass index (BMI-a measurement of obesity risk) at thirty months. However, these effects were decreased if the pregnant woman had higher social support during the flood (Kroska et al 2017). Therefore, providing increased social support to pregnant women during and after natural disasters may have positive consequences for generations after the specific traumatic event.…”
Section: Intergenerational Stress Resilience and Recovery: The Bodymentioning
confidence: 99%